Pengaruh Konsumsi Tablet Fe dengan Air Jeruk Nipis terhadap Peningkatan Kadar Hb Ibu Hamil di Klinik Aulia Khalik Medika - Geri Febriyanto; Yan Permadi; Bramtama Sukma Mulia; Sri Hidayati; Yulia Yulia; Hastalina Hastalina (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
The Maternal Mortality Rate (MMR) is an indicator of the success of a country's services. Around 830 women die from complications of pregnancy or childbirth worldwide. Low public awareness about the health of pregnant women is one of the determining factors in mortality. One indication that is often experienced by pregnant women is anemia. Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in them is lower than normal or does not meet the body's needs. Anemia that is often experienced by pregnant women is caused by iron deficiency. To fulfill iron in the body, blood-added supplements are needed and also other nutrients such as vitamins. This study aims to determine Effect of consumption of Fe tablets with lime juice on increasing Hb levels in pregnant women. The research method used was a quasi-experimental design with a non-randomized control group pretest posttest design. Sampling was done by means of purposive sampling.The results of the bivariate analysis showed that there was an effect of consuming Fe tablets and lime juice with an increase in hemoglobin levels of pregnant women with a significance value of 0.000 (p value <0.05). The conclusion is that there is an effect of consuming Fe tablets and lime juice with increasing hemoglobin levels of pregnant women.